2017
DOI: 10.1242/jcs.195164
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative FastFUCCI assay defines cell cycle dynamics at a single-cell level

Abstract: The fluorescence ubiquitination-based cell cycle indicator (FUCCI) is a powerful tool for use in live cells but current FUCCI-based assays have limited throughput in terms of image processing and quantification. Here, we developed a lentiviral system that rapidly introduced FUCCI transgenes into cells by using an all-in-one expression cassette, FastFUCCI. The approach alleviated the need for sequential transduction and characterisation, improving labelling efficiency. We coupled the system to an automated imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 39 publications
(45 reference statements)
2
72
0
3
Order By: Relevance
“…5A). This may explain why it was previously found that the interference with the DNA replication origin activity enhanced the response of cells to paclitaxel (16).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…5A). This may explain why it was previously found that the interference with the DNA replication origin activity enhanced the response of cells to paclitaxel (16).…”
Section: Discussionmentioning
confidence: 91%
“…While the blockage in S phase is expected after gemcitabine exposure, due to depletion of the nucleotide pool required for DNA duplication, cells treated with nab-paclitaxel were expected to arrest in mitosis or late G2 phase due to defects in spindle elongation. However, recent data have revealed that cells treated with paclitaxel often proceeded through mitosis into the next interphase, where the majority of cell deaths occurred (16). In particular, nab-paclitaxel seemed to interfere with the very early stages of the S phase in PDAC cells (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…A problem with the original FUCCI was the need to use two separate plasmids, which may not be equally expressed, thereby confusing the color specificity of the various cell-cycle phases. FastFUCCI was subsequently developed, which has an all-in-one expression cassette that has all FUCCI genes under the control of a single promoter, resulting in their equal expression; these different FUCCI systems are compared in Figure 2 [21].…”
Section: Fucci Images Cell-cycle Dynamics Of Cancer Cells In Real-timementioning
confidence: 99%
“…Further investigations into the field of stem cell differentiation may yield more clinically applicable therapeutics. Mouse models with fluorescence ubiquitination cell cycle indicator (FUCCI) markers (Zielke and Edgar, 2015; Koh et al, 2017) and Lgr5-GFP positive cells (Bramhall et al, 2014), have been used to find small molecules capable of inducing stem cell differentiation into hair cell progenitors. Through the use of these models, a small molecule CHIR99021, a GSK inhibitor capable of inducing cochlear progenitor cells has been identified (Roccio et al, 2015).…”
Section: Specialized Sensory Cell Regenerationmentioning
confidence: 99%